Ventricular assist devices in paediatric cardiomyopathy and congenital heart disease: An analysis of the German National Register for Congenital Heart Defects. (15th November 2021) - Lammers, Astrid Elisabeth; Sprenger, Katharina Sofie; Diller, Gerhard-Paul; Miera, Oliver; Lebherz, Corinna; Helm, Paul C.; Abdul-Khaliq, Hashim; Asfour, Boulos; Ewert, Peter; Bauer, Ulrike M.M.; Kehl, Hans-Gerd; Humpl, Tilman; et al.
Abstract: Background: Ventricular assist devices (VAD) are increasingly used in patients with end-stage heart failure due to acquired heart disease. Limited data exists on the use and outcome of this technology in children. Methods: All children (<18 years of age) with VAD support included in the German National Register for Congenital Heart Defects were identified and data on demographics, underlying cardiac defect, previous surgery, associated conditions, type of procedure, complications and outcome were collected. Results: Overall, 64 patients (median age 2.1 years; 45.3% female) receiving a VAD between 1999 and 2015 at 8 German centres were included in the analysis. The underlying diagnosis was congenital heart disease (CHD) in 25 and cardiomyopathy in 39 children. The number of reported VAD implantations increased from 13 in the time period 2000–2004 to 27 implantations in the time period 2010–2014. During a median duration of VAD support of 54 days, 28.1% of patients experienced bleeding complications (6.3% intracerebral bleeding), 14.1% thrombotic (10.9% VAD thrombosis) and 23.4% thromboembolic complications (including cerebral infarction in 18.8% of patients). Children with cardiomyopathy were more likely to receive a cardiac transplantation (79.5% vs. 28.0%) compared to CHD patients. Survival of cardiomyopathy patients was significantly better compared to the CHD cohort ( p < 0.0001). Multivariate Cox-proportional analysis revealed a diagnosis of CHD (hazard ratio [HR] 4.04, p = 0.001), age at VAD implantation (HR 1.09/year, p = 0.04) and the need for pre-VAD extracorporeal membrane oxygenation (ECMO) support (HR 3.23, p = 0.03) as independent predictors of mortality. Conclusions: The uptake of VAD therapy in children is increasing. Morbidity and mortality remain high, especially in patients with congenital heart disease and those requiring ECMO before VAD implantation. Highlights: The uptake of VAD therapy in children is increasing. Morbidity and mortality remain high. Congenital heart disease and ECMO before VAD implantation are risk factors.